Analisis Faktor Yang Berhubungan Dengan Tingkat Kepuasan Pada Ibu Bersalin Di Puskesmas Tanara Kabupaten Serang : Analysis of Factors Associated with the Level of Satisfaction of Mothers Giving Birth at the Tanara Community Health Center, Serang Regency - Pratiwi, Fitri Dewi; Mulyana, Dede Sri (Dohara POAJ, 2023)
Introduction: The ability of the health center to meet the needs of patients can be a measure of whether or not patients are satisfied with the services provided. Some of the factors causing low patient satisfaction include psychological factors which include service quality and attitude, as well as physical factors including room facilities. Methods: This is a quantitative analytic study with a cross-sectional design. Samples were all women who gave birth at the Tanara Health Center in Serang Regency with a total of 63 samples with a total sampling technique. The research instrument used a questionnaire. Primary data were analyzed using the chi-square statistical test. Results: The results of the univariate analysis showed that 76.2% of delivery women experienced satisfaction, good service quality was 77.8%; good attitudes of midwives was 69.8%; and 85.7% had good room facilities. The results of the bivariate analysis showed that there was a significant relationship between service quality (p = 0,000); attitudes of midwives (p = 0,000) and room facilities (p = 0,000) with maternal satisfaction. Discussion: The attitude of midwives has the highest chance of satisfaction with the delivery women with an OR of 120.400. It is hoped that midwives can improve their performance, especially in giving attention and being more friendly and friendly.